Adverse events following immunization surveillance on two types of enterovirus 71 vaccines: A real-world comparative study in China - Yiqing Zhu; Yihan Wang; Jinghui Wang; Yafei Wang; Li Sun; Shiheng Cui; Jing Li; Yu Guo (Human Vaccines & Immunotherapeutics)
To comprehensively assess the safety and difference of two types of EV71 vaccines: EV71-Vero, produced using Vero cells and EV71-H2, using human diploid cells. Our research included children of the recommended age who voluntarily received the EV71 vaccine in Hebei Province from 2019 to 2023. Detailed data on adverse events following immunization (AEFI) were collected, analyzed and compared for EV71-Vero and EV71-H2 vaccines. With 477 AEFI reported, the reported rate was 14.21 per 100,000 doses. Most cases occurred in infants under one year of age (45.91%). No significant differences in the AEFI reported rate were found between two types of EV71 vaccines across various demographic. However, a higher number of AEFI was reported in children under 1-year old following EV71-Vero compared to EV71-H2 with a reversal in 4–5 years- group (χ2 = 13.90, p = .01). The prognosis of cured took higher proportion for EV71-Vero than for EV71-H2 while inversely with improved outcome. The EV71 vaccine is advisable recommend to the appropriate age children to prevent EV7l infection. Both the EV71-Vero and EV71-H2 vaccines have good safety profiles. The reported AEFI, primarily high fever and allergic reactions, showed no significant differences in reported rates or case characteristics between the two types.